Knowledge transfer process analysis on the 3-day MTV exit youth jam - Francisco, Keziah Suzaine W.
On September 13-15, 2013, a 3-day MTV Exit Youth Jam was held in Davao City where 25 youths were chosen and trained to become their Davao Youth Ambassadors. This research was conducted to determine whether or not three days was enough to for the youth ambassadors to be equipped with knowledge regarding the issue and the campaign against human trafficking. It also identified the communication tools and strategies used and the critical factors that affected the transfer of knowledge in the Youth Jam. Semi-structured interviews and focus group discussion was conducted, and an online questionnaire was sent to the youth ambassadors in order to gather data. The method of analysis employed in this study is Szulanski?s Critical Factors of Knowledge Transfer. The study revealed that the communication tools used are Power Point presentations, face to face interaction and activities while the strategies are mostly lecture/seminar style of discussion. It has also been revealed that the youth ambassadors are more motivated when it comes to gaining knowledge since it is more personal, and experience and emotion-based. On the other hand, youth ambassadors especially those who are not familiar with the topic have a hard time understanding those with explicit knowledge since those are more technical and facts-based. Lastly, the results implied that the three days were not enough for the conduct of the youth jam, or it would have been enough if the topic on human trafficking was localized; if there was an allotted time for interaction and sharing of opinions; and if the backgrounds of each youth ambassadors were checked in order to adjust the communication tools and approach for each topic.